THE TEACHING TECHNIQUE OF INDONESIAN IN MADRASAH IBTIDAIYAH: LEARNING FROM MI SURUH 1 PLUS, MIFTAHUL ULUM AND MA'ARIF PULUTAN - Nurul Maghfiroh; Maslikhah Maslikhah; Khusna Widhyahrini (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2020)
By language skill possessed, students can blow on a variety of knowledge to appreciate literature and to develop themselves sustainably. But there are still many students who do not like Bahasa Indonesia n lessons because of being boring. They were not boring the teacher can use some methods.  The Teaching technique was a concrete implementation in the learning process for students.  The teachers can change their methods anytime for the same subject.  The purpose of this study was to find out various kinds of teaching methods to teach Bahasa Indonesia in the 2nd and 5th Grade in Madrasah Ibtidaiyah (MI) or Primary School level.  This research used the qualitative method by interview semi-structured and questionnaire on the theme.  The research obtained that MI Suruh 1 Plus used 10 techniques for 2nd Grade and 14 techniques for 5th Grade; MI Miftahul Ulum used 10 techniques for 2nd Grade and 13 techniques for 5th Grade, and MI Maarif Pulutan used 10 techniques for 2nd Grade and 14 techniques for 5th Grade. Variations in techniques used in 3 schools still use almost the same technique, which is different for each school in applying classroom learning techniques according to the material during learning. Keterampilan berbahasa yang dimiliki siswa mampu menggali berbagai pengetahuan untuk mengapresiasi sastra, dan mengembangkan diri secara berkelanjutan. Tetapi masih banyak siswa yang tidak menyukai pelajaran Bahasa Indonesaia dengan alasan membosankan. Agar tidak bosan guru dapat menggunakan beberapa teknik. Teknik Mengajar adalah implementasi konkrit dalam proses pembelajaran bagi siswa. Para guru dapat mengubah metode mereka untuk mata pelajaran yang sama. Tujuan dari penelitian ini adalah untuk mengetahui berbagai macam teknik pengajaran untuk mengajar Bahasa Indonesia  di kelas 2 dan 5 di tingkat Madrasah Ibtidaiyah (MI). Penelitian ini menggunakan metode kualitatif dengan wawancara semi struktur dan angket. Penelitian ini memperoleh bahwa MI Suruh 1 Plus menggunakan 10 teknik untuk kelas 2 dan 14 teknik untuk kelas 5; MI Miftahul Ulum menggunakan 10 teknik untuk Kelas 2 dan 13 teknik untuk Kelas 5; dan MI Maarif Pulutan menggunakan 10 teknik untuk Kelas 2 dan 14 teknik untuk Kelas 5. Variasi teknik yang digunakan di 3 sekolah masih menggunakan teknik yang hampir sama yang membedakan tiap sekolah dalam mengaplikasi teknik pembelajaran dikelas disesuaikan dengan materi saat pembelajaran.